1997
DOI: 10.1099/00221287-143-7-2449
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic factor secreted by Streptococcus pyogenes is a heat-stable nuclease requiring His122 for activity

Abstract: The gene encoding a mitogenic factor, termed MF, was cloned from Streptococcus pyogenes and the recombinant M F was overexpressed in Escherichia coli. Both the natural and recombinant M F had heat-resistant nuclease activity. The nuclease activity of MF was characterized using the recombinant protein. MF showed endonuclease activity, digesting ssDNA, dsDNA and tRNA. The optimal pH for the DNase activity of MF was 9.5. The DNase activity was enhanced approximately tenfold by the simultaneous presence of two div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 35 publications
1
37
0
Order By: Relevance
“…We considered the possibility that two virtually identical genes might co-exist in the S. pyogenes genome, though this was excluded in the wild-type strain we studied as only a single 1 kb fragment hybridized to the mf probe following NdeI genomic digestion. Identity at the protein level was first suggested by Iwasaki et al (1997), who demonstrated that recombinant MF had DNase activity in addition to the mitogenic actions shown in earlier work. A subsequent study from Sweden showed that the two proteins were immunologically identical using polyclonal antisera (Eriksson et al, 1999).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…We considered the possibility that two virtually identical genes might co-exist in the S. pyogenes genome, though this was excluded in the wild-type strain we studied as only a single 1 kb fragment hybridized to the mf probe following NdeI genomic digestion. Identity at the protein level was first suggested by Iwasaki et al (1997), who demonstrated that recombinant MF had DNase activity in addition to the mitogenic actions shown in earlier work. A subsequent study from Sweden showed that the two proteins were immunologically identical using polyclonal antisera (Eriksson et al, 1999).…”
Section: Discussionmentioning
confidence: 73%
“…Recombinant MF is reported to have nuclease activity and separate studies have shown that MF and the streptococcal nuclease DNase B share identical immunologic epitopes (Eriksson et al, 1999 ;Iwasaki et al, 1997), suggesting that the two proteins are equivalent. Antibodies to both DNase B and MF have been detected in patients recovering from streptococcal sepsis, showing that these proteins are synthesized by pathogenic streptococci during infection (Gerber et al, 1980 ;Norrby-Teglund et al, 1994a).…”
Section: Introductionmentioning
confidence: 99%
“…The individual effects of the speC and speF genes in the pathogenesis of invasive GAS infection are unclear. SpeF is known as a multifunctional protein that has mitogenic, superantigenic, nuclease, and vascular permeabilization activities (16,28). SpeX (also called SMEZ3), a superantigen, preferentially stimulates V␤8…”
Section: Discussionmentioning
confidence: 99%
“…Four immunologically and electrophoretically distinct nucleases, designated DNases A, B, C, and D, have been previously identified in S. pyogenes supernatant fluids (45,46). DNase D is encoded by the sdaD gene (35), and MF is thought to be identical to the protein previously described as DNase B (16). It is unclear if DNA entry nuclease (ORF 226) is identical to enzymes previously designated DNase A or C. ORF 226 is approximately 30% identical to several nucleases, including streptodornase (accession number X84793), EndA of Streptococcus pneumoniae (23), and MF (accession number D13428).…”
Section: Figmentioning
confidence: 99%